2022
DOI: 10.1021/acscatal.2c02769
|View full text |Cite
|
Sign up to set email alerts
|

Fully Exposed Platinum Clusters on a Nanodiamond/Graphene Hybrid for Efficient Low-Temperature CO Oxidation

Abstract: A fundamental understanding of the active sites in heterogeneous catalysts is extremely important in the development of effective catalysts. In general, it is difficult to identify the catalytically active sites due to their structural complexity, including the size and specific atomic configurations. In this paper, we prepare different Pt species (single atoms, fully exposed clusters, and nanoparticles) on a nanodiamond/graphene (ND@G) hybrid support to understand their evolution in structure for low-temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…Thus, the simulation of graphite and GCN models were able to describe the experimental initial catalytic activity by employing and as reactivity descriptors, in agreement with recent computational studies on Pt clusters supported on carbonaceous materials. 115 Furthermore, the comparison between Ir/graphite and Ir/GCN models in terms of and agrees with the higher catalytic activity observed (4024 h −1 and 3654 h −1 , respectively) for the sub-nanometric Ir supported on graphite.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Thus, the simulation of graphite and GCN models were able to describe the experimental initial catalytic activity by employing and as reactivity descriptors, in agreement with recent computational studies on Pt clusters supported on carbonaceous materials. 115 Furthermore, the comparison between Ir/graphite and Ir/GCN models in terms of and agrees with the higher catalytic activity observed (4024 h −1 and 3654 h −1 , respectively) for the sub-nanometric Ir supported on graphite.…”
Section: Resultssupporting
confidence: 79%
“…Thus, the simulation of graphite and GCN models were able to describe the experimental initial catalytic activity by employing and 𝐺𝐶𝑁 𝐼𝑟 -𝐼𝑟 as reactivity descriptors, in agreement with recent computational studies on Pt clusters supported on carbonaceous materials. 115 Furthermore, the comparison between Ir/graphite and Ir/GCN models in terms Previous studies on the hydrous hydrazine decomposition performed over supported Ir catalysts demonstrated that the metal clusters' catalytic activity may decline due to the adsorption of residual decomposition intermediates, leading to poisoning of the active sites and catalysts deactivation. The authors were able to demonstrate that this can be substantially reduced when H 2 is admixed to the reaction environment, namely, in presence of a stronger reducing atmosphere favouring a further decomposition of the residual adsorbates.…”
Section: Catalytic Activity and Poisoning Resistancementioning
confidence: 99%
“…As shown in Figure d, the Pt L3 -edge X-ray absorption near-edge structure (XANES) shows that the average valence state of Pt in 2Pt/ZrO 2 is the highest compared to 1Pt/ZrO 2 and 5Pt/ZrO 2 , which is supported by the higher absorption edge energy and white line intensity. , The Fourier transform (FT) profiles of the k 3 -weighted extended X-ray absorption fine structure (EXAFS) spectra (Figure e) and the structural parameters are listed in Table S2 in the ESM. For 1Pt/ZrO 2 , two peaks are observed at 1.6 and 2.6 Å, associated with the first shell of Pt–O and Pt–Pt scattering, respectively. , The Pt–O coordination peak becomes stronger, and the Pt–Pt coordination peak becomes weaker for 2Pt/ZrO 2 .…”
Section: Resultsmentioning
confidence: 93%
“…As shown in Figure 2d, the Pt L3-edge X-ray absorption near-edge structure (XANES) shows that the average valence state of Pt in 2Pt/ZrO 2 is the highest compared to 1Pt/ZrO 2 and 5Pt/ZrO 2 , which is supported by the higher absorption edge energy and white line intensity. 49,50 The Fourier transform (FT) profiles of the k 3 -weighted extended X-ray absorption fine structure (EXAFS) spectra (Figure 2e) and the structural parameters are listed in Table S2 The EPR spectrum of 1Pt/ZrO 2 has two weak EPR signals, as shown in Figure 2f. The signal appearing at g = 2.002 is the characteristic indicator of oxygen vacancies (OVs).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Utilizing the abundant defects with phenolic groups on the surface of ND@G, a library of ADMs has been synthesized in our work (Figure ). In addition, benefiting from a distinctive difference of atomic number/composition contrast (Z-contrast) between metal atoms and carbon substrate, a transmission electron microscope (TEM), particularly the scanning transmission electron microscopy (STEM) technique, can provide higher resolution images to identify the geometric structures. This is helpful to visually observe the structure changes of ADMCs under in situ conditions. In addition, the surface properties of ND@G can be largely modified by doping and functionalization, even the creation of metals or metal–oxide interfaces to anchor atomically dispersed active metals.…”
Section: Atomically Dispersed Metals On Nanodiamond and Its Derivativesmentioning
confidence: 99%